(untitled) (Journal of Economics and Management Research, 2023)
يهدف هذا البحث إلى تسليط الضوء على واقع الشمول المالي في الدول العربية، من خلال الإطلاع على أهم مؤشراته وعرض مختلف الاستراتيجيات التي تم اعتمادها من اجل تعزيزه في إطار تحقيق أهداف التنمية المستدامة. وقد توصل البحث إلى وجود تباين بين الدول العربية فيما يخص مؤشرات الشمول المالي، حيث أن دول الخليج العربي تشهد تطور متقدم في مختلف الخدمات والمنتجات المالية، بينما دول المغرب العربي لم تصل بعد إلى المستوى المطلوب، ما يفرض عليها تبني إستراتيجية واضحة المعالم. The aim of this research is to shed light on the reality of financial inclusion in the Arab countries, by reviewing its most important indicators and presenting the various strategies that have been adopted in order to enhance it within the framework of achieving sustainable development goals. The research found a discrepancy between the Arab countries with regard to indicators of financial inclusion, as the Arab Gulf countries are witnessing an advanced development in various financial services and products, while the Arab Maghreb countries have not yet reached the required level, which forces them to adopt a clear strategy.